Pharmacological Inhibition of STING/TBK1 Signaling Attenuates Myeloid Fibroblast Activation and Macrophage to Myofibroblast Transition in Renal Fibrosis - Zeng, Haimei; Gao, Ying; Yu, Wenqiang; Liu, Jiping; Zhong, Chaoqun; Su, Xi; Wen, Shihong; Liang, Hua (Frontiers in Pharmacology, 2022)
Renal fibrosis is an important pathological biomarker of chronic kidney disease (CKD). Stimulator of interferon genes/TANK binding kinase 1 (STING/TBK1) axis has been identified as the main regulator of innate immune response and closely related to fibrotic disorder. However, the role of STING/TBK1 signaling pathway in kidney fibrosis is still unknown. In this study, we investigated the effect of pharmacological inhibition of STING/TBK1 signaling on renal fibrosis induced by folic acid (FA). In mice, TBK1 was significantly activated in interstitial cells of FA-injured kidneys, which was markedly inhibited by H-151 (a STING inhibitor) treatment. Specifically, pharmacological inhibition of STING impaired bone marrow-derived fibroblasts activation and macrophage to myofibroblast transition in FA nephropathy, leading to reduction of extracellular matrix proteins expression, myofibroblasts formation and development of renal fibrosis. Furthermore, pharmacological inhibition of TBK1 by GSK8612 reduced myeloid myofibroblasts accumulation and impeded macrophage to myofibroblast differentiation, resulting in less deposition of extracellular matrix protein and less severe fibrotic lesion in FA-injured kidneys. In cultured mouse bone marrow-derived monocytes, TGF-β1 activated STING/TBK1 signaling. This was abolished by STING or TBK1 inhibitor administration. In addition, GSK8612 treatment decreased levels of α-smooth muscle actin and extracellular matrix proteins and prevents bone marrow-derived macrophages to myofibroblasts transition in vitro. Collectively, our results revealed that STING/TBK1 signaling has a critical role in bone marrow-derived fibroblast activation, macrophages to myofibroblasts transition, and kidney fibrosis progression.